CD109 deficiency induces osteopenia with an osteoporosis‐like phenotype in vivo. (16th May 2018) - Mii, Shinji; Hoshino, Akiyoshi; Enomoto, Atsushi; Murakumo, Yoshiki; Ito, Masako; Yamaguchi, Akira; Takahashi, Masahide
Abstract : Osteoporosis is a global public health problem that is increasing along with an aging population. A major determinant of osteoporosis is high bone turnover, which results from osteoclast activation. CD109 is a glycosylphosphatidylinositol‐anchored glycoprotein, a deficiency that leads to a psoriasis‐like skin inflammation in mice. Although the expression of CD109 has been reported in mouse pre‐osteoclast cells, its function in osteoclasts in vivo remains largely unknown. To investigate the physiological role of CD109 in bone metabolism, we analyzed bones from wild‐type and CD109‐deficient adult mice. Micro‐computed tomography analysis of the femur (thigh bone) showed that bone volume was lower in CD109‐deficient mice than in wild‐type mice. Bone histomorphometric analysis showed not only a reduction in bone volume but also an increase in bone turnover in CD109‐deficient mice as compared with wild‐type mice. Additionally, we measured serum levels of several markers of bone turnover and found a significant increase in the N‐terminal telopeptide of type I collagen, a bone resorption marker, as well as alkaline phosphatase, a bone formation marker, in CD109‐deficient mice. These results indicate that CD109 deficiency induces a high‐turnover, osteoporosis‐like phenotype, which suggests that CD109 plays a role in bone metabolism in vivo. Abstract : We analyzed CD109‐deficient mice, focusing on their bones. We showed CD109 expression in osteoblasts as well as osteoclasts and found that CD109 deficiency induces loss of bone volume in adult mice with high bone turnover, a phenotype that resembles type I osteoporosis. These results suggest that CD109 plays a role in bone metabolism in vivo and that CD109 may be a therapeutic target for osteolytic diseases.